Pengaruh Komitmen Organisasi, Lingkungan Kerja, Dan Kompetensi Terhadap Kinerja Karyawan Bagian Akuntansi Dengan Kepuasan Kerja Sebagai Variabel Moderating ( Pada Perusahaan Perbankan Di Kota Pekanbaru ) - Indah Dwi Lestari; Vince Ratnawati; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to know the influence significant of a organizational commitment, work environment, and competency of the employees performance in the accounting department with job satisfaction as moderating variable. The population in this study is a employees in the accounting department in the banking companies in Pekanbaru. The sampling method used in this study is the random sampling method. The stastical method used to test the research hypothesis is multiple regression using SPSS 17 software.The results of this research show that the variables that significantly affect the employee's performance in the accounting department of banking companies is variable organizational commitment, work environment, and competency. Variable job satisfaction was significantly moderated the effect of organizational commitment on employees performance in the accounting department. And variable job satisfaction was not significantly moderate the effect of the work Environment and competency on employees performance in the accounting department.Keywords: employees performance, organizational commitment, work environment, competency and job satisfaction.